Newly designed PdRuBi/N-Graphene catalysts with synergistic effects for enhanced ethylene glycol electro-oxidation. (10th February 2016) - Li, Tengfei; Huang, Yiyin; Ding, Kui; Wu, Peng; Abbas, Syed Comail; Ghausi, Muhammad Arsalan; Zhang, Teng; Wang, Yaobing
Graphical abstract: We rationally design and synthesize a ternary PdRuBi/NG catalyst with significantly enhanced catalytic activity with synergetic effect of Ru and Bi towards ethylene glycol electro-oxidation. Abstract: Palladium (Pd)-based catalysts are appealing electro-catalysts for alcohol oxidation reaction in fuel cell, but still not efficient as the complicated oxidation process and sluggish kinetic. Here we rationally design and synthesize a PdRuBi/NG tri-metallic catalyst with space synergetic effect for enhanced ethylene glycol electro-oxidation, in which both Ru and Bi in the catalyst are synergistic effective in promoting catalytic activity of Pd catalytic interlayer by electronic effect and surface modification mechanism respectively. It shows 4.2 times higher peak current density towards ethylene glycol electro-oxidation than commercial Pd/C catalyst, and the catalytic durability is also greatly improved.